A new polymorphic Phrynobatrachus (Amphibia: Anura: Phrynobatrachidae) from western Nigeria - Rödel, Mark-Oliver; Onadeko, Abiodun B.; Barej, Michael F.; Sandberger, Laura (Zootaxa, 2012)
We describe a new small Phrynobatrachus species from western Nigeria, the eastern-most part of the Upper Guinea bio-diversity hotspot. The new species exhibits a combination of unique morphological characters and a belly without pattern.Morphologically it is characterised by small size, compact roundish body with a round and short snout, large eyes, absenceof an eyelid cornicle, presence of a conspicuous row of warts with pores on the upper mandible, absence of discs on toeand finger tips, well developed webbing, larger warts on forehead and inter-orbital space and a pair of, sometimes indis-tinct, elongated chevron like ridges on the back. Analysis of mitochondrial 16S rRNA revealed that the new species differsfrom 33 other West and Central African species of the genus by a minimum distance of 6.6%. Genetically the new speciesis most similar to Phrynobatrachus ghanensis, P. guineensis and P. phyllophilus, all being endemic to the western part of the Upper Guinea forest zone.